An alternative planning paradigm for coastal landscapes and tourism. Spatial metrics as indicators for planning coastal tourism landscapes - Botequilha-Leitão, André (2018)
Coastal urbanization dynamics in the Algarve are intimately related with tourism, which dominates the regional economy. We present part of the results of a research project in the coastal landscapes of Algarve, focusing on land use and land change, particularly urban sprawl around Faro, one of the highest concentrations of tourism resorts in the region. We performed a diachronic analysis (1990-2000) based on Corine Land Cover data. We combined contingence tables and landscape metrics. A parsimonious suite of these spatial metrics were selected in order to be easily combined as to derive results with a straightforward interpretation, and moving windows technique facilitated the task in identifying gradients of landscape heterogeneity. Land use planning must pay more attention to tourism, adopting combined spatial approaches, monitor initiatives, and do better plans. Metrics are good indicators for this purpose.